Bibliometric analysis of sepsis and gut microbiota: Trends from 2014 to 2024 - Zhang, Runze; Huo, Chenxing; He, Chenming; Luo, Jielian; Shan, Yunan; Lu, Jiamin; Zhang, Jirong; Zhang, Wen; Fang, Bangjiang (Frontiers in Microbiology, 2025)
BackgroundSepsis is a life-threatening condition characterized by organ dysfunction resulting from a dysregulated host response to infection, with pathological mechanisms closely linked to imbalances in the intestinal flora. While the gut microbiota influences sepsis progression through metabolic and immune regulation, systematic analyses of research trends remain limited. This bibliometric study comprehensively evaluates the sepsis and gut microbiota field from 2014 to 2024.MethodsWe analyzed 944 English-language articles from the Web of Science (WOS) Core Collection using CiteSpace, VOSviewer, and other software tools. The bibliometric assessments included analysis of publication trends, collaborative networks, geographic distributions, journal impact, and keyword clustering.ResultsA total of 944 publications included contributions from 5,901 authors across 69 countries. These works were published in 405 journals, and cited a total of 45,932 references. The focus of research has transitioned from early topics such as “necrotizing enterocolitis” and “premature infants” to more recent interests on “short-chain fatty acids” (SCFAs) and “Candida albicans.” Futhermore, emerging topics include “sepsis-associated encephalopathy,” with microbiology and critical care medicine identified as interdisciplinary core fields.ConclusionThe therapeutic potential of the gut microbiota in sepsis is increasingly recognized. Future research should prioritize microbial-targeted therapies, immune-barrier-metabolic network regulation, and integrated traditional Chinese–Western medicine approaches.